Elliptic flow in a strongly interacting normal Bose gas - Fletcher, R; Man, J; Lopes, R; Christodoulou, P; Schmitt, J; Sohmen, M; Navon, N; Smith, R; Hadzibabic, Z (American Physical Society, 2018)
We study the anisotropic, elliptic expansion of a thermal atomic Bose gas released from an anisotropic trapping potential, for a wide range of interaction strengths across a Feshbach resonance. We show that this hydrodynamic phenomenon is for all interaction strengths fully described by a microscopic kinetic model with no free parameters. The success of this description crucially relies on taking into account the reduced thermalizing power of elastic collisions in a strongly interacting gas, for which we derive an analytical theory. We also perform time-resolved measurements that directly reveal the dynamics of the energy transfer between the different expansion axes.